Detection of the Petrosquamosal Sinus in Chronic Otitis Media Using High‐Resolution CT. Issue 3 (13th June 2013) - Hiraumi, Harukazu; Yamamoto, Akira; Yamamoto, Norio; Sakamoto, Tatsunori; Ito, Juichi
Abstract : Objective: To evaluate the prevalence of the persistent petrosquamosal venous sinus in patients with chronic otitis media using a high‐resolution CT scan. Study Design: Retrospective chart review. Setting: Tertiary referral center. Subjects and Methods: Eighty‐four patients older than 6 years of age underwent surgery (in a total of 92 ears) for chronic otitis media at Kyoto University Hospital, Department of Otolaryngology‐Head and Neck Surgery. We used high‐resolution CT scans to evaluate the prevalence and size of persistent petrosquamosal sinuses, as well as their relative position to the middle fossa. Results: A petrosquamosal sinus was detected in 42 (45.7%), a higher frequency than in ears without chronic otitis media (10.3%). The diameter of the sinuses was <1.0 mm in 20 ears, 1.0 mm to 2.0 mm in 17 ears, and >2.0 mm in 5 ears. The petrosquamosal sinus was positioned inferior to the lowest part of the middle fossa in 10 ears. Conclusion: The petrosquamosal sinus was detected frequently in high‐resolution CT scans in patients with chronic otitis media. In approximately half of the patients, the sinus was larger than 1 mm in diameter and may be encountered during mastoidectomy.